Effect of In-ovo Injection of L-Arginine on Hatchability, Chick Quality, Performances and Muscle Histology of Native Chicken - M Azhar; U Sara; S Wahyuni (Indonesian Center for Animal Research and Development (ICARD), 2022)
This study aimed to determine the effect of in-ovo injection of L-arginine on hatchability, chick quality, performances, and muscle histology of native chicken. In-ovo injection was carried out on the 10th day. A total of 375 fertile eggs with an average weight ranged 39-43 g were grouped into 5 treatments. The first treatment was without injection (negative control), the second treatment was injection of NaCl solution 0.9% (positive control), the third treatment was injection of L-arginine solution 0.5 g per 100 ml of NaCl 0.9% (0.5%, m/v) The fourth treatment was injection of 1.0 g L-arginine solution per 100 ml of NaCl 0.9% (1.0%, m/v), and the fifth treatment was injection of 1.5 g L-arginine solution per 100 ml of NaCl 0.9% (1.5%, m/v). The injection was carried out at the pointed area of the egg in a vertical position (pointed below, blunt above). The Injection was carried out with a depth of 10 mm from the eggshell using an automatic injector. The results showed that all treatments produced the same hatchability. In-ovo injection of L-arginine has a beneficial effect on chick quality and post-hatch performance, the concentration of L-arginine solution used did not cause embryo death. In-ovo injection of 0.5% L-arginine increased hatching weight, weekly body weight, muscle mass, and myofiber size.